The West Pacific anemone-shrimp Ancylomenes speciosus (Okuno, 2004) (Crustacea: Decapoda: Palaemonidae)—a species complex or single species? - Ďuriš, Zdeněk; Fišarová, Karolína; Šobáňová, Anna; Lin, Chia-Wei (Zootaxa, 2024)
A series of specimens identifiable as the anemone-associated shrimp Ancylomenes speciosus (Okuno, 2004) are reported here from New Caledonia, NE Australia, and SW Taiwan. Detailed morphological remarks and figures of the specimens are provided. All examined adults are morphologically very similar, males and subadults differ from adult females mainly by their unarmed second cheliped fingers and the more elongated sixth pleomere. The New Caledonian and Australian specimens differ by their colour pattern from adult Taiwanese specimens. The genetic divergences among specimens are 5.1–6.4% for COI and 2.5–3.7% for 16S genes. The interregional genetic divergences between those specimens are generally 2.5–3 times lower than the interspecific divergences revealed for three other DNA-analysed species (A. kobayashii, A. luteomaculatus, and A. magnificus). Considering the lower minimal values of genetic divergences, the morphological similarity between regions, the occurrence of both colour morphs in Taiwan, and reported photos of intermediate colour forms, the examined shrimps are provisionally regarded as representatives of a single species A. speciosus. However, based on the maximal divergence values, the examined specimens might also represent a species complex. The true taxonomic status of these specimens will thus need a more detailed morphological and molecular examination of further specimens from more western-Pacific locations.